THE INFLUENCE OF TIKTOK PROMOTIONAL MEDIA, INSTAGRAM PROMOTIONAL MEDIA, AND FACEBOOK PROMOTIONAL MEDIA ON PURCHASE DECISIONS MIXUE ICE CREAM & TEA - Rizky Amelia Rahma Safitri; Rini Rahayu Kurniati; Khoiriyah Trianti (Universitas Islam Malang, 2023)
The research carried out aims to understand Do Tiktok Promotional Media, Instagram Promotional Media, and Facebook Promotional Media influence consumer purchasing decisions for Mixue Ice Cream & Tea? This type of research is quantitative using methods Non-Probability Sampling and the sample is Purposive e Sampling . Sampling was carried out using the Cochran formula, because the population size is relatively large and cannot be known with certainty so the number collected was 100 respondents . Testing data that can be tested on IBM SPSS version 25 . The results of the research state that the independent variables Tiktok Media Promotion (X1), Instagram Media Promotion (X2), Facebook Media Promotion (X3) are influenced by Purchase Decisions (Y). The results of the F test state that F calculated > F table (18.613 > 2.698) and the value is significant ( . 0.00 . < 0.05 . ). The value of the Coefficient of Determination states that the TikTok Promotion Media, Instagram Promotion Media and Facebook Promotion Media variables influence the Purchase Decision variable by 34.8% simultaneously . The final number (100% - 34.8% = 65.2%) contained other factors that influenced the research carried out .